Semantic Modification of the Mitkov Algorithm for Anaphora Resolution - Marchenko, O.O. (Штучний інтелект, 2012)
The article is dedicated to modern algorithm of pronominal anaphora resolution. Anaphora resolution should be considered in a wider range of problems related with language ambiguity resolution, for instance: entity recognition, reference analysis and in general case, of course, semantic analysis of natural language text. We can render conclusion from stated above that anaphora resolution is possible only on semantic level of natural language analysis. The main purpose of this work is development of semantic heuristics for finding the most probable antecedent corresponding to anaphora with analysis of sentence context. The proposed algorithm gives about 5% improvements in comparison to the standard Mitkov algorithm. Робота присвячена аналізу алгоритму розв’язання займенникової анафори. Розв’язання анафори має бути розглянуто в рамках широкого кола проблем лінгвістичної неоднозначності, наприклад: розпізнавання сутностей тексту, аналіз посилань та, в загальному випадку, семантичний аналіз текстів природною мовою. Із зазначеного вище можна зробити висновок, що розв’язання анафори можливе лише на семантичному рівні аналізу природної мови. Головною метою цієї роботи є розробка семантичної евристики для пошуку найбільш імовірного антецедента, що відповідає анафорі, із застосуванням аналізу контексту речень. Запропонований алгоритм дає покращення близько 5% порівняно зі стандартним алгоритмом Міткова. Работа посвящена анализу алгоритма решения местоименной анафоры. Решение анафоры должно быть рассмотрено в рамках широкого круга проблем лингвистической неоднозначности, например: распознавание сущностей текста, анализ ссылок и, в общем случае, семантический анализ текстов на естественном языке. Из указанного выше можно сделать вывод, что решение анафоры возможно только на семантическом уровне анализа естественного языка. Главной целью этой работы является разработка семантической эвристики для поиска наиболее вероятного антецедента, соответствующего анафоре, с использованием анализа контекста предложений. Предложенная модификация алгоритма дает улучшение около 5% по сравнению со стандартным алгоритмом Миткова.